2011
DOI: 10.1149/1.3633304
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial and Uniaxial Compressive Stress Implemented in Ge(Sn) pMOSFET Channels by Advanced Reduced Pressure Chemical Vapor Deposition Developments

Abstract: Three advanced architectures for ultimate progress in Ge p-Metal Oxide Semiconductor Field Effect Transistors are discussed in this paper. Different routes for stress implementations in Ge channels, either biaxial or uniaxial, are proposed by advanced selective Chemical Vapor Deposition techniques. Selective SiGe Strained Relaxed Buffer growth in Shallow Trench Isolation is first discussed to implement biaxial compressive strained Ge Quantum Wells on top of it. Next, innovative GeSn chemical vapor deposition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The graph also shows the h c values as predicted by the Matthews and Blakeslee 17 GeSn layers grown under such conditions (i.e. low T CVD 6 ) are in a metastable state, where kinetic barriers 19 have likely delayed the formation and/or motion of misfit dislocations (MDs).…”
Section: Gesn Strain Relaxation Mechanismmentioning
confidence: 90%
See 1 more Smart Citation
“…The graph also shows the h c values as predicted by the Matthews and Blakeslee 17 GeSn layers grown under such conditions (i.e. low T CVD 6 ) are in a metastable state, where kinetic barriers 19 have likely delayed the formation and/or motion of misfit dislocations (MDs).…”
Section: Gesn Strain Relaxation Mechanismmentioning
confidence: 90%
“…Ge 1-x Sn x alloys are intriguing materials, with a potentially major impact on future-generation microelectronic and photonic applications due to a sizable improvement of the charge transport properties 1,2 and to a transition to a direct bandgap semiconductor for sufficiently high Sn concentrations. 3 In addition, the possibility to tune the lattice parameter and bandgap of GeSn by varying the alloy composition opens new routes for stress implementation [4][5][6] and heterogeneous integration. 7 In order to gain a better understanding of the fundamentals and the tailoring of the material properties, it is indispensable to accurately assess (i) the alloy composition x and (ii) its influence on the GeSn relaxed cubic lattice constant a 0 GeSn Stoichiometric data would be assessable via X-ray diffraction if Vegard's law: 8 a Ge 1−x Snx 0 = a Ge 0 (1 − x) + a Sn 0 x + b GeSn x(1 − x) [1] (with the inclusion of an appropriate bowing parameter b GeSn to account for deviations from a pure linear interpolation between the Ge and Sn lattice constants a 0 Ge and a 0 Sn ) would correctly model the lattice constants as a function of composition -which is usually the case for compound semiconductors.…”
mentioning
confidence: 99%
“…Again, clear channel modulation has been observed indicating a good passivation route without Ge interlayer to use Ge 1-x Sn x in future pMOSFET channels. 36 The CV performance is improved after a forming gas anneal at 300 • C as illustrated by figure 6b. We concluded that the surface Fermi-level of the measured Ge 0.93 Sn 0.07 MOSCAP does not reach the conduction band edge due to poor gate modulation efficiency and high D it at the upper half of the bandgap.…”
Section: Device Conceptsmentioning
confidence: 94%
“…33,34 Sn segregation to the Ge 1-x Sn x -surface during 27 gate formation can be avoided by using low processing temperatures, 33 a Si-passivation, 34 or a Ge-passivation layer eventually combined with an additional GeO 2 passivation. [35][36][37] At imec, we used solid source Molecular Beam Deposition (MBD) 35,37 and Atomic Layer Deposition (ALD) 36,37 to deposit Al 2 O 3 gate oxides on p-Ge (001)/Ge 1-x Sn x and p-Ge (001)/Ge 1-x Sn x /Ge epi-layers grown by either Molecular Beam Epitaxy (MBE) or CVD. The Ge 1-x Sn x containing MBE layers have been kindly provided by the Nagoya University.…”
Section: Device Conceptsmentioning
confidence: 99%
“…Tensile-strained germanium has been studied as a possible laser material due to its nearly-direct bandgap [1,2] and its compatibility with conventional silicon integrated circuit fabrication [3][4][5][6]. Theoretically, a tensile strain of 0.7% (hydrostatic) or 1.4% (biaxial) could produce a direct bandgap in Ge [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%